2016
DOI: 10.1016/j.actpsy.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Do humans spontaneously take the perspective of others?

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
123
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(148 citation statements)
references
References 18 publications
15
123
7
Order By: Relevance
“…Namely, the level to which people engage in level-1 PT in the dot perspective task has been found to be influenced by participants' emotional states (Bukowski & Samson, 2016;Todd & Simpson, 2016), as well as the identity of the avatar: one that is representing the self or a stranger (Mattan et al, 2015). The selectivity of implicit PT contradicts approaches (Cole, Atkinson, Le, & Smith, 2016;Santiesteban, Catmur, Hopkins, Bird, & Heyes, 2014) postulating that perspective interference reflects a 'blind', domain-general, non-social process.…”
Section: Discussionmentioning
confidence: 98%
“…Namely, the level to which people engage in level-1 PT in the dot perspective task has been found to be influenced by participants' emotional states (Bukowski & Samson, 2016;Todd & Simpson, 2016), as well as the identity of the avatar: one that is representing the self or a stranger (Mattan et al, 2015). The selectivity of implicit PT contradicts approaches (Cole, Atkinson, Le, & Smith, 2016;Santiesteban, Catmur, Hopkins, Bird, & Heyes, 2014) postulating that perspective interference reflects a 'blind', domain-general, non-social process.…”
Section: Discussionmentioning
confidence: 98%
“…Further research has focused on whether the perspective may not be a spontaneous phenomenon. If this is the case, then RAS would be only modulated by perceptual characteristics of the cue, while perspective taking would be due to top-down processes [18][19][20][21]. These authors noted that the human avatar employed by Samson et al [7] was unable to generate an attentional shift when the target discs were presented within 300 ms from the presentation of the cue.…”
Section: Introductionmentioning
confidence: 99%
“…Santiesteban and colleagues observed prolonged reaction time even in experiments where the avatar was replaced by an arrow, suggesting that arrow cues have the same attention orienting effect as does the avatar [27, 28]. Modifications of the dot perspective task (such as use of transparent and opaque barriers or the use of transparent and opaque goggles) yielded results inconsistent with spontaneous perspective taking [29]. Though, Furlanetto et al [30] using the dot perspective task demonstrated that the consistency effect occurred only when the avatar wore the transparent goggles but not for the opaque goggles.…”
Section: Introductionmentioning
confidence: 99%